2008
DOI: 10.1007/s11740-008-0078-4
|View full text |Cite
|
Sign up to set email alerts
|

Further potentials of CAQ tools for fault handling in automotive manufacturing processes

Abstract: The example of automotive body-in-white production is used to illustrate further potentials for automated fault handling in operative quality control. A review of pertaining literature on process modeling and control suggests some trends and future practices in research and industry. The paper discusses current results of a research project aimed at devising novel process and knowledge modeling concepts for online fault diagnosis and recovery. The proposed approach differentiates between three different tasks:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Various research projects in collaboration with production facilities of OEMs in Germany have shown that the expenses concerning scrap and rework engage a large amount reaching up to 2% of the overall production budgets in body-in-white [10]. The most common sources of product faults are identified in material failures [2] and geometrical inaccuracies [11,12] during manufacturing processes.…”
Section: State-of-the-art and Identification Of Problemmentioning
confidence: 99%
“…Various research projects in collaboration with production facilities of OEMs in Germany have shown that the expenses concerning scrap and rework engage a large amount reaching up to 2% of the overall production budgets in body-in-white [10]. The most common sources of product faults are identified in material failures [2] and geometrical inaccuracies [11,12] during manufacturing processes.…”
Section: State-of-the-art and Identification Of Problemmentioning
confidence: 99%